Self-Live or KOL-Live? Selling Channel Selection in A Platform Supply Chain Considering Return Policies - Wu, Jingrong; Zhang, Rong; Liu, Bin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
Live-streaming sales in e-commerce have become increasingly indispensable. This paper examines the factors influencing supply chain members’ choice between self-run (channel S) and KOL live streaming (channel K) in live commerce and investigates how different return policies—return refund (RR) and returnless refund (RL)—affect the platform’s channel selection. It shows that brands prefer the live-streaming channel under both return policies. Under return refund, the platform favors live streaming when the KOL’s influence is weak or strong, but avoids self-run live streaming when the KOL’s influence is moderate. Under the returnless refund, the platform chooses self-run live streaming when the KOL’s influence is moderate, and the proportion of opportunists is low. However, as the proportion of opportunists rises, the platform avoids self-run live streaming. Only when the KOL’s influence is negligible, and the proportion of opportunists is high, will the brand choose to return a refund.